2013
DOI: 10.1002/j.0022-0337.2013.77.9.tb05585.x
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perceptions of Materials and Techniques Used at European Dental Schools in the Education of Fixed Prosthodontics

Abstract: The aim of this study was to explore the materials and procedures used by students in dental schools across Europe for teaching ixed prosthodontics. An online questionnaire, containing twenty-eight dichotomous, multiple-choice, and Likert scale rating questions, was sent to students in forty dental schools. After excluding dental schools in which less than 10 percent of the students responded, 775 questionnaires from ten schools remained for statistical analysis. Among these respondents, acrylic resin teeth we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 20 publications
(24 reference statements)
1
12
0
2
Order By: Relevance
“…There are probably many valid and effective models for building competence in prosthodontics. If we used the clinical competence data regarding the fixed partial dentures as a proxy of the students’ global rating of their fixed prosthodontics education, using a 0–10 range, our results (6.6±1.5 for PBL students; 7.6±1.1 for traditional students) were within the average range of 5.6±2.2 reported by students at Ljubljana University (Slovenia) to 8.0±1.1 found among students at Nijmegen University (Netherlands) reported by Brand et al 20 Moreover, we did not find any significant differences regarding gender, which is in agreement with Walley et al's findings 18 …”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…There are probably many valid and effective models for building competence in prosthodontics. If we used the clinical competence data regarding the fixed partial dentures as a proxy of the students’ global rating of their fixed prosthodontics education, using a 0–10 range, our results (6.6±1.5 for PBL students; 7.6±1.1 for traditional students) were within the average range of 5.6±2.2 reported by students at Ljubljana University (Slovenia) to 8.0±1.1 found among students at Nijmegen University (Netherlands) reported by Brand et al 20 Moreover, we did not find any significant differences regarding gender, which is in agreement with Walley et al's findings 18 …”
Section: Discussionsupporting
confidence: 77%
“…As pointed out by Scott, there is still large variability in the number of credits assigned to prosthodontics across Spanish dental schools (from 18 to 30 ECTS) 19 . Furthermore, Brand et al's study found considerable variation among ten European dental schools (from Finland, France, Netherlands, Slovenia, Sweden, and the UK) regarding the teaching of fixed prosthodontics, concluding that dental curricula varied in prosthodontics training with regard to the year in which teaching begins (from year 2 to 5) and in the materials and techniques used for fixed prosthodontics, as well as the compulsory number of treatments students must perform before graduating 20 …”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained by Brand et al who conducted research on students' assessment of materials and methods in learning of fixed prosthodontics among several dental medicine study programs in Europe. ( 19 ) The results show that dental medicine courses of study which start earlier with preclinical learning have higher ratings in terms of preparedness of students for clinical work, as well as a higher overall rating of courses in fixed prosthodontics. It is interesting to notice that assessment of preparedness of students for clinical work, as well as overall assessment of quality of learning did not correlate with the year of study of the students who participated in the study.…”
Section: Discussionmentioning
confidence: 91%
“…It has previously been reported that there is widespread variation in the number of indirect restorations that UK dental schools expect students to complete prior to qualification [15,31,32]. Some schools reported that they do not have a minimum number of fixed dental prostheses that their students have to complete because their program is competency-based.…”
Section: Discussionmentioning
confidence: 99%
“…Some schools reported that they do not have a minimum number of fixed dental prostheses that their students have to complete because their program is competency-based. Whether schools have minimum requirements or not, it is essential that students are clearly informed of any requirements with sufficient notice in order for them to be achieved [32]. Bristol Dental School is currently implementing a new curriculum and a major component of this will be to move all practical restorative manikin teaching to earlier within the curriculum.…”
Section: Discussionmentioning
confidence: 99%